Constructing and Characterizing TiAlN Thin Film by DC. Pulsed Magnetron Sputtering at Different Nitrogen/Argon Gas Ratios - Raaif, Mohamed (JOURNAL OF ADVANCES IN PHYSICS, 2018)
In this survey, the magnetron sputtering with Dc. Pulsed mode was embroiled to deposit TiAlN thin film on AISI 316 as a substrate. All the plasma magnetron parameters were fixed excluding the nitrogen gas ratio which was varied from 10% to 50% with step interval of 10% with respect to argon. The structure, mechanical, tribological and electrochemical peculiarities of TiAlN films were studied. The TiAlN deposition rate is decreased in regard with increasing the nitrogen gas ratio where, the film thickness recorded a maximum value of 3 µm at nitrogen gas ratio of 10 %. X-ray configurations demonstrated the formation of solid solution phase of TiAlN with different orientations. The TiAlN coating has (111) preferred orientation at 10 and 20% nitrogen gas ratios while has (200) preferred orientation at 30- 50% nitrogen gas ratios. The crystallite size is decreased with increasing the nitrogen gas ratio. The results depicted that, the microhardness of TiAlN film is increased with decreasing the nitrogen gas ratio and recorded a maximum value of approximately 850 HV0.015 at 10% N2. Additionally, the tribological properties of the coated AISI 316 with TiAlN are enhanced compared with the uncoated sample. The wear volume loss of the coated sample at 10% N2 has a value of nearly 9X104 µm3 which is low in comparison with AISI 316 substrate that has a value of 4.5X106 µm3. The corrosion resistance of all TiAlN coatings was better than the uncoated sample. It was demonstrated; the change in nitrogen gas ratio affected the physicochemical characteristics of the TiAlN coating.